2007
DOI: 10.5897/ajb2007.000-2433
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and spatial root biomass and water use efficiency of four forage legumes in semiarid northwest China

Abstract: Shoot biomass continued to increase from April to November for all the four legumes. In November, the root biomass for milkvetch and alfalfa accounted for about 2.93 and 2.30% of the total biomass (root plus shoot) respectively, while in sainfoin and L. davurica it accounted for 6.00 and 4.44% respectively. There were significant differences between the four legumes in WUE, and the order was same as shoot biomass, ranked as milkvetch>alfalfa>sainfoin>L. davurica. The seasonal and yearly high shoot biomass and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 14 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…However, the decrease of the leaf area in the presence of the water deficit was resulted in a reduction of the dry matter accumulation (Martinielli and Da Silva, 2011). Our results showed an increase of the root/shoot ratio as was mentioned by Bingcheng et al (2007) and Slama et al (2008). This indicated that water stress has entailed a severe decrease in the biomass air part than the root biomass.…”
Section: Discussionsupporting
confidence: 63%
“…However, the decrease of the leaf area in the presence of the water deficit was resulted in a reduction of the dry matter accumulation (Martinielli and Da Silva, 2011). Our results showed an increase of the root/shoot ratio as was mentioned by Bingcheng et al (2007) and Slama et al (2008). This indicated that water stress has entailed a severe decrease in the biomass air part than the root biomass.…”
Section: Discussionsupporting
confidence: 63%
“…Dubach and Russelle (1994) compare alfalfa and birdsfoot trefoil and conclude that these two legumes differ in their mechanisms of N contributions to soil, alfalfa transferring more through root decomposition while trefoil transfers more through nodule decomposition, but differences between TA B L E 3 Compiled data extracted from overlapping grazing study (Maughan et al, 2014) showing crude protein differences between alfalfa and sainfoin legumes in 2012 the two legumes were negligible. Although we did not assess root:shoot, a study comparing alfalfa and sainfoin showed that root:shoot biomass was significantly greater in sainfoin than alfalfa (Bingcheng, Shan, Li, & Jiang, 2007).…”
Section: Field Experimentsmentioning
confidence: 99%